Determinants of Financial Management Skills Among Indonesia’s Gen Z - Iqbal Raditya Maulana; Sadamsyah; Miranda Tanjung (PT Mattawang Mediatama Solution, 2024)
New to the workforce, Gen Z's financial management skills are crucial. This study explores how factors like financial literacy, family education from family, financial attitude, hedonism lifestyle and financial knowledge on Generation Z’s financial management skills. A survey of 257 Gen Z members explored financial management skills using Structural Equation Modelling (SEM) analysis via SmartPLS 3.0 software. Financial education from family, hedonism lifestyle, and financial knowledge has no significant impact on Generation Z’s financial management skills. however, financial literacy and financial attitude have an impact. Research implications This Research's findings impact policymakers, financial institutions and academic. Academic institutions should provide sufficient financial education for Generation Z to empower them on financial choices. Policymakers must encourage prudent financial habits among Generation Z. This research focuses on Generation Z who are new to the workforce and many of the variations in the determinants of financial management skills have not been explored in previous research.